ANALISIS FAKTOR DETERMINAN KINERJA KEBERLANJUTAN DAN KONSEKUENSI EKONOMIS SAHAM TERINDEKS IDX ESGL - ., Zulmaita; Warsini, Sabar; Rahmawati, Lia; Rana Amany, Fithriya (Ekonomi & Bisnis, 2024)
Along with the increasing global commitment to sustainability performance as stated in the Sustainable Development Goals (SDGs) program, the launch of the IDX ESG Leaders index by the Indonesia Stock Exchange is an attractive option for investors. This study aims to find empirical evidence of determinants of the sustainability performance of IDX ESG Leaders stocks as measured by the quality of information presented in sustainability reports and test the economic consequences. Factors suspected to be determinants of sustainability performance are the effectiveness of independent board supervision, company scale, profit growth, and leverage. Testing the economic consequences is done by examining the relationship between sustainability performance and firm value. The research was conducted on IDX ESG Leaders constituent stocks for March−September 2023. The data used is secondary data in financial reports, annual reports, and sustainability reports from 2020−2023. Hypothesis proof using panel data regression. The results of this study indicate that the independent commissioner variable has a negative effect on the quality of sustainability reports. The variables of company size, profit growth, and leverage have a negative effect on the quality of sustainability reports. Meanwhile, the variable quality of sustainability reports has a positive impact on firm value. Keywords: IDX ESG Leaders, company size, profit growth, leverage, sustainability report quality, firm value